2000
DOI: 10.1111/j.1745-7599.2000.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review Of Current Nursing Faculty Practice

Abstract: PURPOSE To critically examine the current literature on nursing faculty practice, using the National Organization of Nurse Practitioner Faculties (NONPF) Guidelines for Evaluation of Faculty Practice, and to examine faculty practice models' strengths, weaknesses, and barriers. DATA SOURCES Thirty‐five articles describing models of faculty practice were identified through an exhaustive search on CINAHL and Medline. Two NONPF monographs on nursing faculty practice were used as guidelines for the critical review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In a critical review of 35 articles, Sawyer and colleagues [43] concluded that, by 2000, faculty practice had become an integral component of faculty role expectations at most schools of nursing. Successful faculty practice models are well described in the literature [4467].…”
Section: Resultsmentioning
confidence: 99%
“…In a critical review of 35 articles, Sawyer and colleagues [43] concluded that, by 2000, faculty practice had become an integral component of faculty role expectations at most schools of nursing. Successful faculty practice models are well described in the literature [4467].…”
Section: Resultsmentioning
confidence: 99%
“…Dissonance is an overall theme in the literature reviewed on faculty practice and stems from the perceived threats/risks of faculty practice (Sawyer et al. 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Models of faculty practice were reviewed to identify a model that could be adopted to facilitate faculty practice in the institution studied. The literature tends to highlight the expertise of those who have attempted to incorporate a model (Sawyer et al. 2000, Council of Deans of Nursing and Midwifery, Australia and New Zealand 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the absence of formal recognition within workload allo-cation models, nurse academics are often faced with the option of ''moonlighting'' in the clinical setting to engage in nursing practice. 5 At the other end of the spectrum descriptive accounts 6 identify how faculty practice can be integrated within academic roles through models such as academic nurse managed centres (ANMCs). Such centres provide opportunities for practice, research and education while acknowledging the interrelated nature of knowing, teaching, practice and service.…”
Section: Introductionmentioning
confidence: 99%